Sports nutrition interventions: A systematic review of behavioural strategies used to promote dietary behaviour change in athletes. (1st July 2020) - Bentley, Meghan R.N.; Mitchell, Nigel; Backhouse, Susan H.
Abstract: Designing and implementing successful dietary interventions is integral to the role of sports nutrition professionals. Despite this, no review has evaluated sports nutrition interventions and consequently their active ingredients are not defined. This systematic review aimed to identify the behavioural strategies used in sports nutrition interventions and to explore any relationship between the strategies employed and intervention effects. SPORTDiscus, MEDLINE, CINAHL, PubMed, and SCOPUS were searched for behavioural interventions that aimed to change athletes' dietary behaviour. Behavioural interventions were eligible for inclusion provided pre and post-measures of dietary intake were reported. The protocol adheres to Preferred Reporting Items for Systematic reviews and Meta-Analyses Protocols (PRISMA-P). Each study was coded against the "Template for Intervention Description and Replication" (TIDieR) checklist and the Behaviour change technique (BCT) taxonomy v1. Only 19 BCTs are currently employed within sports nutrition interventions suggesting that 80% of the available BCTs are not being used. Only three studies were theory informed and the standard of reporting across all studies requires substantial improvement. However, the majority of studies reported changes in athletes' dietary behaviour post-intervention. This review highlights an absence of evidence-informed approaches defining the professional practice of sports nutrition and illuminates a limited application of BCTs within the sports nutrition field. Consequently, the authors provide a framework and guide for intervention development to increase rigour and effectiveness of future sports nutrition interventions. PROSPERO registration number: CRD42018072283.